Effect of glycerol and sorbitol plasticizers on physical and thermal properties of sugar palm starch based films - Sanyang, Muhammed Lamin; Salit, Mohd Sapuan; Jawaid, Mohammad; Ishak, Mohamad Ridzwan; Japar, Sahari (WSEAS Press, 2015)
The aim of this study was to characterize and compare the effect of glycerol and sorbitol plasticizers on physical and thermal properties of sugar palm starch (SPS) films. Film samples were prepared using conventional casting technique. Sorbitol plasticized SPS films (S-SPS) have higher thickness and density. Whereas, the moisture content and solubility of SPS films containing glycerol (G-SPS) were higher than those of S-SPS. The addition of sorbitol to SPS films elevated the thermal degradation temperature to higher values and thus, increased the thermal stability of S-SPS than G-SPS.